Concurrent logic programming as a hardware description tool - Dotan, Y.; Arazi, B. (IEEE transactions on computers, 1990)
The possibility of developing hardware description languages (HDLs) based on the principles of logic programming is discussed. The specific logic programming language used to demonstrate this possibility is Flat Concurrent Prolog (FCP). It is shown explicitly how FCP naturally satisfies the commonly accepted fundamental requirements of a hardware description language. It is then demonstrated how FCP overcomes known disadvantages of the highly acclaimed VHDL. Some other parallel logic programming languages beside FCP are also presented briefly, and the possibility of using them for hardware description is discussed.< >